Antioxidant and inhibitory activities of α-amylase, α-glucosidase, and G6Pase from Smallanthus sonchifolius tuber extract as a potential antidiabetic agent - Wahyu Widowati; Rita Tjokropranoto; Roro Wahyudianingsih; Fen Tih; Penny Setyawati Martioso; Dani Dani; Vera Vera; Faradhina Salfa Nindya; RR. Annisaa Saraswati; Nadya Isabella Andretti; Nonny Oktaviany Putri; Fryda Cahya Saputra (Journal of HerbMed Pharmacology)
Introduction: Diabetes mellitus (DM) is a chronic condition with free radicals and carbohydrate-hydrolyzing enzymes playing key roles in its progression. Yacon or Smallanthus sonchifolius (Poepp.) H.Rob, a low-sugar crop, has shown promising bioactivities. This research aimed to explore the antidiabetic and antioxidant potential of yacon tuber extract (YTE). Methods: YTE’s antioxidant and enzyme inhibitory activities were assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) at concentrations of 6.25, 12.5, 25, 50, 100, 200 µg/mL, hydrogen peroxide (H₂O₂) scavenging activity at 12.5, 25, 50, 100, 200, 400 µg/mL, 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and ferric reducing antioxidant power (FRAP) at 1.56, 3.13, 6.25, 12.5, 25, 50 µg/mL. The inhibition of α-amylase, α-glucosidase (6.25, 12.5, 25, 50, 100, 200 µg/mL), and glucose 6-phosphatase (G6Pase) (5.51, 11.03, 22.6, 44.12, 88.24, 176.47 µg/mL) was also assessed. Phytochemical analysis identified key bioactive compounds, and IC₅₀ values were determined to quantify YTE’s antioxidant and antidiabetic potentials. Results: YTE contained flavonoids, terpenoids, triterpenoids, and phenolic compounds. It showed highest antioxidant activity (P<0.05) in DPPH, ABTS, H₂O₂, and FRAP assays at 200, 50, 400, and 50 µg/mL, respectively, compared to the other concentrations. In DPPH, H₂O₂, and ABTS assays, the IC₅₀ values were 105.77 μg/mL, 726.64 μg/mL, and 61.03 μg/mL, respectively. FRAP activity was 338.68 μM/μg Fe (II) at 50 µg/mL. YTE also inhibited α-amylase, α-glucosidase, and G6Pase with IC₅₀ values of 174.95 μg/mL, 222.17 μg/mL, and 112.51 μg/mL, respectively. Conclusion: YTE exhibited significant antioxidant properties and inhibited carbohydrate-hydrolyzing enzymes, indicating its potential as an antidiabetic agent.